استخدام الطرائق الضبابية لحل نماذج الخزين مع تطبيق عملي - عبد الجبار خضر بخيت; عباس حسين بطيخ; خالد وليد عطا (Journal of Madenat Alelem University College, 2016)
The inventories of the important things in many companies, accounting for 50% of the capital invested overall with the intensity of pressure goal to reduce the overall costs of the other types of uncertainties (Blur), so we will provide in this research economic order quantities College (production economic quantities) to reach the optimal batch size Almillbh (FEOQ) when they are all landmarks in case you are not sure where it is converted to one period and then get on the economic batch size. One of the main problems faced by the management of any organization is how to make the best decision if the decision is to maximize profits or minimize costs or reduce the cost of storage. Stockpiling is the most important resource of the enterprise resources they need, especially if it affects the lives of citizens, so it became a trend to keep storage and control it by the companies of very important topics.